Cordyceps poluscapitis sp. nov., an ant-pathogenic fungus from Guizhou, China - Peng, Xing-Can; Xiao, Yuan-Pin; Zhang, Yan; Chomnunti, Putarak; Tangtrakulwanich, Khanobporn; Wen, Ting-Chi (Phytotaxa, 2023)
A species of entomopathogenic fungi was found on ants in Guizhou Province, China. It is described as Cordyceps poluscapitis (Cordycipitaceae), a novel species with both a sexual and an asexual morph. Cordyceps species are characterized by producing brightly coloured, fleshy stromata and long, filiform ascospores. Cordyceps poluscapitis is unique in that it is parasitic on ants and produces multiple-septate conidia. Multi-gene phylogeny based on combined sequence data of 6-loci genes (ITS, SSU, LSU, TEF, RPB1 and RPB2) confirmed that it is a new species in Cordyceps.